2017
DOI: 10.1027/0269-8803/a000177
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quality of Sleep and Emotional Empathy

Abstract: Abstract. Sleep loss is known to severely disturb individuals’ mood and emotion processing. Here, we tested the hypothesis that quality of sleep is predictive of individuals’ performance on a task evaluating emotional empathy. We tested 34 healthy undergraduate students [19 males, mean (SD) age = 21.82 (3.26) years; mean (SD) education = 14.98 (1.91) years] recruited through the University of Calgary research participation system. We collected objective (actigraphy) and subjective (questionnaires and self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…Although in the existing literature the effects of sleep quality on BOLD activity in mesolimbic areas are mixed, in our most recent work focusing solely on the emotional component of empathy, we identified that poorer sleep quality was associated with a reduced tendency to share the emotions of others (i.e., blunted emotional empathy (Guadagni et al., ). Here, we attempt to replicate our previous findings of poor sleep quality producing blunted emotional empathy, as well as to identify its possible neural correlates in a healthy young population.…”
Section: Introductionmentioning
confidence: 66%
“…Although in the existing literature the effects of sleep quality on BOLD activity in mesolimbic areas are mixed, in our most recent work focusing solely on the emotional component of empathy, we identified that poorer sleep quality was associated with a reduced tendency to share the emotions of others (i.e., blunted emotional empathy (Guadagni et al., ). Here, we attempt to replicate our previous findings of poor sleep quality producing blunted emotional empathy, as well as to identify its possible neural correlates in a healthy young population.…”
Section: Introductionmentioning
confidence: 66%
“…Supporting this hypothesis, sleep-deprived individuals and habitually poor sleepers demonstrate impaired empathetic sensitivity, which involved sensing the emotion state of individuals in picture slides 98,99 . Sensing the internal homeostatic status of the body, and thereby tracking one’s own affective state, requires interoceptive processing within a network that includes the insula, mPFC and amygdala 100 .…”
Section: Aversive Stimulus Processingmentioning
confidence: 89%
“…We then used the ISI global scores to determine participants’ group membership: individuals who had scores greater than eight, and had insomnia-like symptoms according to the ISI manual, were assigned to the poor sleep group (N=10, 5 females, mean age =20.9 years, SD age =3.0 years), and those with scores less than eight were assigned to the control group (N=14, 3 females, mean age =21.43 years, SD age =2.9 years). We decided to use such subjective measure for classifying participants’ sleep quality based on the evidence that subjective sleep measures are more sensitive to detect and define poor sleep quality as compared to actigraphy measures, particularly in subjects that lie motionless in bed [27], [28]; moreover, in a recent study we collected a variety of objective and subjective sleep measures and used a principal components analysis to provide evidence that subjective sleep measures including the ISI were the factors that best explained behavioural performance among individuals [29]. In the present study, in addition to the ISI, we calculated the global score for the PSQI by summing participants' responses from the seven subcomponents of the questionnaire; higher PSQI scores were indicative of poorer sleep quality.…”
Section: Methodsmentioning
confidence: 99%